Особенности создания физической модели процесса образования элементов стружки при обработке глубоких отверстий - Маршуба, Вячеслав Павлович (НТУ "ХПИ", 2007)
The physical model of the process of chip elements' formation, when materials are processing by cutting, is offered. On the basis of offered physical model, it is possible to create the general math-ematical model, which describes the process of cutting in different materials. Usage of this physical model will allow determining necessary conditions for processing of deep bores with maximum productivity when processing components from different materials.
Keywords: обработка механическая; резание; деформация пластическая; сопротивление; слой поверхностный; сила трения; теплообразование; инструмент режущий